Bacillus subtilis Attenuates Hepatic and Intestinal Injuries and Modulates Gut Microbiota and Gene Expression Profiles in Mice Infected with Schistosoma japonicum - Lin, Datao; Song, Qiuyue; Zhang, Yishu; Liu, Jiahua; Chen, Fang; Du, Shuling; Xiang, Suoyu; Wang, Lifu; Wu, Xiaoying; Sun, Xi (Frontiers in Cell and Developmental Biology, 2021)
Parasitic infection can induce pathological injuries and impact the gut microbiota diversity and composition of the host. Bacillus subtilis (B. subtilis) is a nonpathogenic and noninvasive probiotic bacterium for humans and other animals, playing an important role in improving the host immune system’s ability to respond to intestinal and liver diseases and modulating gut microbiota. However, whether B. subtilis can impact biological functions in Schistosoma japonicum-infected mice is unclear. This study used oral administration of (OA) B. subtilis to treat mice infected with S. japonicum. We evaluated changes in the gut microbiota of infected mice using 16S rRNA gene sequencing and differentially expressed gene profiles using transcriptome sequencing after OA B. subtilis. We found that OA B. subtilis significantly attenuated hepatic and intestinal pathological injuries in infected mice. The gut microbiota of mice were significantly altered after Schistosoma japonicum infection, while OA B. subtilis remodel the diversity and composition of gut microbiomes of infected mice. We found that the Schistosoma japonicum-infected mice with OA B. subtilis had an overabundance of the most prevalent bacterial genera, including Bacteroides, Enterococcus, Lactobacillus, Blautia, Lachnoclostridium, Ruminiclostridium, and Enterobacter. Transcriptomic analysis of intestinal tissues revealed that OA B. subtilis shaped the intestinal microenvironment of the host responding to S. japonicum infection. Differentially expressed genes (DEGs) were classified into KEGG pathways between Schistosoma japonicum-infected mice and those without included cell adhesion molecules (CAMs), intestinal immune network for IgA production, hematopoietic cell lineage, Fc epsilon RI signaling pathway, Th1 and Th2 cell differentiation, Th17 cell differentiation, calcium signaling pathway, Fc gamma R-mediated phagocytosis, chemokine signaling pathway, phospholipase D signaling pathway, NF-kappa B signaling pathway, B cell receptor signaling pathway, pancreatic secretion, and phagosome. In conclusion, our findings showed that OA B. subtilis alleviates pathological injuries and regulates gene expression, implying that B. subtilis supplementation may be a potential therapeutic strategy for schistosomiasis. Our study may highlight the value of probiotics as a beneficial supplementary therapy during human schistosomiasis, but further studies are needed.